Television-assisted approach in teaching civics and culture and pupil achievement - Adriano, Ma. Corazon V. (2006)
The research was conducted to determine if television-assisted approach could be effective in teaching Civics and Culture in the elementary level. The sample consisted of two Grade Two classes of Sto. Nino Elementary School in Marikina City. The experimental group was taught using the television-assisted approach, with the program Pamana, while the control group was instructed using the conventional way. A researcher-constructed Achievement test was used to determine the effectiveness of the program. It is concluded that the television-assisted approach helped students gain significantly more knowledge that those taught using the traditional approach. Thus, television-assisted approach can be an effective tool in teaching Civics and Culture in the elementary level.